Overhead transmission line connection fitting preparation method and connection fitting

By using 35CrMo matrix material and thermal spraying process to form the coating and spraying anti-corrosion coating on the surface, the problem of wear and corrosion of overhead transmission line connection metal tools in harsh environments is solved, and significant wear and corrosion resistance is achieved.

CN119663160APending Publication Date: 2025-03-21ELECTRIC POWER RESEARCH INSTITUTE OF STATE GRID SHANDONG ELECTRIC POWER COMPANY +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411776356.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Overhead transmission line connecting metal tools face serious wear and corrosion problems in harsh natural environments, resulting in shorter service life and potential power accidents.

Method used

The 35CrMo matrix material is used to improve strength and toughness through tempering treatment, and a thermal spray powder composed of tungsten carbide powder and nickel alloy powder is used to form a coating through flame spraying process, and anti-corrosion coating is sprayed on the surface to improve wear and corrosion resistance.

Benefits of technology

It significantly improves the wear and corrosion resistance of the connecting metal tool, adapts to strong wind and corrosion environments, extends the service life of the metal tool, and reduces the risk of power accidents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663160A_ABST
    Figure CN119663160A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of overhead transmission line connection fittings, and discloses an overhead transmission line connection fitting preparation method and a connection fitting, and the preparation method comprises the steps: selecting a matrix material of the connection fitting, and carrying out thermal refining to obtain a connection fitting matrix; tungsten carbide powder and nickel alloy powder are selected to form raw material powder, the raw material powder is subjected to impurity removal treatment through a ball milling and screening technology, and thermal spraying powder is obtained; carrying out sand blasting treatment on the surface of the connecting fitting base body, so that the surface of the connecting fitting base body is coarsened; and thermal spraying powder is fed into a powder spraying gun, the joint of the connecting fitting base body is evenly coated with the thermal spraying powder through the flame spraying technology, and a thermal spraying coating is formed. The nickel-coated tungsten carbide powder is used, surface strengthening is carried out on the contact face of the connecting hardware fitting through the thermal spraying technology, the corrosion resistance and the abrasion resistance are improved, the abrasion resistance and the corrosion resistance of the hardware fitting are enhanced through the hardware fitting matching and spraying technology, and it is ensured that the hardware fitting adapts to the strong wind and corrosion environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of overhead power transmission line connection fittings, and in particular to an overhead power transmission line connection fitting preparation method and the connection fitting. Background Art

[0002] During long-term operation, the connecting fittings of overhead transmission lines are often exposed to harsh natural environments, especially in windy areas and corrosive environments, and face more severe challenges. Due to the action of wind, the connecting fittings swing and vibrate under wind loads. This mechanical movement causes frictional contact between the fittings and other components, thereby aggravating their surface wear. At the same time, corrosive gases and liquids in the environment, especially in corrosive atmospheres such as humidity and salt spray, further aggravate the corrosion rate of the fittings. This interaction of corrosion and wear not only shortens the service life of the fittings, but may also lead to fatigue damage at the connection site, increased contact resistance, reduced transmission efficiency, and even cause power accidents.

[0003] Many high-end technologies such as laser cladding and sleeve inserts have been widely used. Laser cladding technology uses a high-power laser beam to melt alloy powder or welding wire and deposit it on the surface of the hardware, thereby forming a protective layer with excellent wear resistance and corrosion resistance. The sleeve insert technology embeds carbide or wear-resistant materials in the key parts of the hardware to form a structure with strong wear resistance. However, although high-end technologies such as laser cladding and sleeve inserts have improved the wear resistance of hardware to a certain extent, they still have problems such as high cost, complex process, and limited scope of application.

[0004] Therefore, how to provide a method for preparing connecting fittings for overhead power transmission lines and connecting fittings is a problem that needs to be solved urgently. Summary of the invention

[0005] The embodiment of the present invention provides a method for preparing a connecting fitting for an overhead power transmission line and a connecting fitting to solve the above-mentioned technical problems existing in the prior art.

[0006] In order to have a basic understanding of some aspects of the disclosed embodiments, a brief summary is given below. This summary is not intended to be a general review, nor is it intended to identify key / important components or to delineate the scope of protection of these embodiments. Its only purpose is to present some concepts in a simple form as a preface to the detailed description that follows.

[0007] According to a first aspect of an embodiment of the present invention, a method for preparing connecting fittings for an overhead power transmission line is provided.

[0008] In one embodiment, the method for preparing the overhead transmission line connection fittings comprises:

[0009] Selecting the base material of the connection fittings, and obtaining the connection fitting base through quenching and tempering treatment;

[0010] Selecting tungsten carbide powder and nickel alloy powder to form raw material powder, and using ball milling and screening process to remove impurities from the raw material powder to obtain thermal spraying powder;

[0011] Performing sandblasting on the surface of the connection hardware base to roughen the surface of the connection hardware base;

[0012] The thermal spraying powder is fed into a powder spray gun, and the connection of the connection hardware substrate is evenly coated by a flame spraying process to form a thermal spray coating;

[0013] An anti-corrosion coating is sprayed on the surface of the connecting hardware base to obtain a wear-resistant and corrosion-resistant connecting hardware.

[0014] In one embodiment, the base material is 35CrMo, and the tempering treatment includes heating to 875°C and then quenching, the tempering temperature after quenching is 550°C, and the tempering time is 2h.

[0015] In one embodiment, the raw material powder is composed of tungsten carbide powder and nickel alloy powder, and the raw material powder is subjected to impurity removal treatment by ball milling and screening process to obtain thermal spraying powder, which includes:

[0016] Select tungsten carbide powder with an average particle size of 30 μm and nickel alloy powder with a particle size of 40-60 μm, mix them to form raw material powder;

[0017] Weigh raw material powder and anhydrous ethanol in a volume ratio of 1:1, add the raw material powder into the anhydrous ethanol, and disperse it by ultrasonic equipment for 30 minutes to obtain a uniformly mixed slurry;

[0018] Pour the mixed slurry into a ball mill, add carbide balls, set the ball mill speed and time, alternately rotate forward and reverse to fully grind the slurry;

[0019] The ball-milled slurry was transferred to a vacuum drying oven and dried under vacuum pressure for 7 hours;

[0020] The dried powder was taken out, and the powder was coarsely screened with an 80-mesh screen, and then finely screened with a 300-mesh screen to obtain a thermal spray powder with impurities removed.

[0021] In one embodiment, the mass fraction of the tungsten carbide powder in the raw material powder is 10%, and the nickel alloy powder is Ni60 powder.

[0022] In one embodiment, the ball milling speed is 80 rpm, the ball milling time is 6 h, the forward rotation time is 1 h, and the reverse rotation time is 0.5 h.

[0023] In one embodiment, the vacuum pressure of the vacuum drying oven is less than 0.1 MPa, and the drying temperature is 70°C.

[0024] In one embodiment, the sandblasting pressure of the sandblasting treatment is 0.4-0.6 Mpa, and the roughness of the surface of the connecting hardware after the sandblasting treatment is 10-15 μm.

[0025] In one embodiment, the step of feeding the thermal spray powder into a powder spray gun and uniformly coating the connection of the connection hardware substrate using a flame spraying process to form a thermal spray coating comprises:

[0026] Preheat the connection hardware base to 300°C;

[0027] The jet flow rate of oxygen-acetylene mixed gas is controlled to feed the thermal spray powder into the powder spray gun, and the compressed air is sprayed at high speed to the connection of the connecting hardware substrate until the entire coating area is evenly coated;

[0028] After waiting for the connection hardware substrate to cool naturally after thermal spraying, the coated area is remelted to densify the coating expressed by the connection hardware. After the remelting is completed, the thermal stress is released by natural cooling to form a thermal spray coating at the connection of the connection hardware substrate.

[0029] In one embodiment, the oxygen flow rate in the oxygen-acetylene mixed gas is 20 L / min, and the acetylene flow rate is 10 L / min.

[0030] In one embodiment, the distance between the powder spray gun and the surface of the connection hardware base is 100 mm, the spray angle is 70°, and the moving speed of the powder spray gun is 10-20 mm per second.

[0031] In one embodiment, the anti-corrosion coating includes a primer and a topcoat, and the primer is a water-based zinc-rich epoxy anti-corrosion coating, and the topcoat is a water-based polyurethane coating.

[0032] According to a second aspect of an embodiment of the present invention, an overhead power transmission line connection fitting is provided.

[0033] In one embodiment, the overhead power transmission line connection fitting comprises a connection fitting base, the connection portion of the connection fitting base is coated with a thermal spray coating, and the surface of the connection fitting base is sprayed with an anti-corrosion coating.

[0034] In one embodiment, the material of the connecting hardware substrate is 35CrMo, the thermal spray coating is flame sprayed, the raw material of the thermal spray coating is thermal spray powder composed of tungsten carbide powder and nickel alloy powder, and the mass fraction of tungsten carbide powder in the thermal spray powder is 10%, and the nickel alloy powder is Ni60 powder.

[0035] In one embodiment, the anti-corrosion coating includes a primer and a topcoat, the primer is a water-based zinc-rich epoxy anti-corrosion coating, and the topcoat is a water-based polyurethane coating.

[0036] In one embodiment, the water-based zinc-rich epoxy anticorrosive coating comprises component A and component B in a mass ratio of 5:4;

[0037] The component A comprises the following raw materials in parts by weight: 15-20 parts of waterborne epoxy curing agent, 75-100 parts of spherical zinc powder, 1-2 parts of defoaming agent and 0.5-2 parts of surface wetting agent;

[0038] The B component includes the following raw materials in parts by weight: 20-25 parts of waterborne epoxy resin, 3-5 parts of polyaniline-modified halloysite nanotubes, 1-2 parts of thickener, 10-15 parts of deionized water, 1-2 parts of defoamer, and 0.5-1 part of anti-flash rust agent.

[0039] In one embodiment, the waterborne polyurethane coating comprises component C and component D in a mass ratio of 5:2;

[0040] The C component includes the following raw materials in parts by weight: 20-25 parts of aqueous hydroxypropyl emulsion, 5-10 parts of aluminum powder, 1-2 parts of titanium dioxide, 3-5 parts of boron nitride nanosheets, 15-20 parts of deionized water, 1-2 parts of wetting and dispersing agent, and 0.3-0.5 parts of defoaming agent;

[0041] The D component comprises the following raw materials in parts by weight: 5-8 parts of isocyanate curing agent and 6-10 parts of propylene glycol methyl ether acetate.

[0042] The technical solution provided by the embodiment of the present invention may have the following beneficial effects:

[0043] 1. By using nickel-coated tungsten carbide powder, the contact surface of the connecting hardware is strengthened through thermal spraying technology to improve corrosion resistance and wear resistance, and the hardware proportioning and spraying process are improved to enhance the wear resistance and corrosion resistance of the hardware, and ensure that it can adapt to strong wind and corrosive environment.

[0044] 2. By using 35CrMo matrix material and optimizing the tungsten carbide content in nickel-based tungsten carbide powder, the wear resistance of the connecting hardware is significantly improved.

[0045] 3. The coating based on Ni-based self-fluxing alloy improves the corrosion resistance of the contact surface of the connecting hardware. The chromium-free zinc-aluminum coating provides excellent corrosion resistance for the non-contact surface of the connecting hardware and is suitable for heavy corrosion environments.

[0046] 4. The flame spraying process has low cost, wide application range, and can evenly apply coatings on surfaces of different shapes and complex shapes.

[0047] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0049] Figure 1 It is a flow chart showing a method for preparing a connecting fitting for an overhead power transmission line according to an exemplary embodiment;

[0050] Figure 2 is a schematic diagram of nickel-based tungsten carbide powder synthesized by ball milling according to an exemplary embodiment;

[0051] Figure 3 is a schematic diagram of a U-shaped hanging ring thermal spraying area according to an exemplary embodiment;

[0052] Figure 4 It is a microhardness distribution diagram of the thermal spray coating of Example 1, Example 2, Comparative Example 1, and Comparative Example 2 shown according to an exemplary embodiment;

[0053] Figure 5 It is a schematic diagram of the electrochemical performance test results of the thermal spray coatings of Example 1, Example 2, Comparative Example 1 and Comparative Example 2 in NaCl solution according to an exemplary embodiment;

[0054] Figure 6 It is a schematic diagram showing a comparison of friction coefficients of thermal spray coatings of Example 1, Example 2, Comparative Example 1, and Comparative Example 2 under the friction and wear conditions of 40N and 6mm grinding balls according to an exemplary embodiment;

[0055] Figure 7 It is a schematic diagram comparing the wear scar profiles of the thermal spray coatings of Example 1, Example 2, Comparative Example 1 and Comparative Example 2 under the friction and wear conditions of 40N and 6mm grinding balls according to an exemplary embodiment. DETAILED DESCRIPTION

[0056] As used herein, the term "plurality" means two or more than two, unless otherwise specified.

[0057] In this document, the character " / " indicates that the preceding and following objects are in an "or" relationship. For example, A / B means: A or B.

[0058] In this article, the term "and / or" is a description of the association relationship between objects, indicating that three relationships may exist. For example, A and / or B means: A or B, or, A and B.

[0059] It should be understood that, although the various steps in the flow chart are displayed in sequence according to the indication of the arrows, these steps are not necessarily executed in sequence according to the order indicated by the arrows. Unless there is a clear description in this article, the execution of these steps is not strictly limited in order, and these steps can be executed in other orders. Moreover, at least a portion of the steps in the figure may include multiple sub-steps or multiple stages, and these sub-steps or stages are not necessarily executed at the same time, but can be executed at different times, and the execution order of these sub-steps or stages is not necessarily to be carried out in sequence, but can be executed in turn or alternately with other steps or at least a portion of the sub-steps or stages of other steps.

[0060] In the absence of conflict, the embodiments of the present invention and the features of the embodiments may be combined with each other.

[0061] Figure 1 An embodiment of a method for preparing connecting fittings for an overhead power transmission line according to the present invention is shown.

[0062] In this optional embodiment, the method for preparing the overhead transmission line connection fittings comprises:

[0063] Step S101, selecting a base material of a connection fitting, and obtaining a connection fitting base through quenching and tempering treatment;

[0064] Step S103, selecting tungsten carbide powder and nickel alloy powder to form raw material powder, and using ball milling and screening process to remove impurities from the raw material powder to obtain thermal spraying powder;

[0065] Step S105, performing sandblasting on the surface of the connection hardware base to roughen the surface of the connection hardware base;

[0066] Step S107, feeding the thermal spray powder into a powder spray gun, and using a flame spraying process to evenly coat the connection of the connection hardware substrate to form a thermal spray coating;

[0067] Step S109, spraying an anti-corrosion coating on the surface of the connection hardware base to obtain a wear-resistant and corrosion-resistant connection hardware.

[0068] In this optional embodiment, the base material is 35CrMo, and the tempering treatment includes heating to 875°C and then quenching, the tempering temperature after quenching is 550°C, and the tempering time is 2h.

[0069] In this optional embodiment, when selecting tungsten carbide powder and nickel alloy powder to form raw material powder, and using ball milling and screening process to remove impurities from the raw material powder to obtain thermal spraying powder, tungsten carbide powder with an average particle size of 30 μm and nickel alloy powder with a particle size of 40-60 μm can be selected and mixed to form raw material powder; the raw material powder and anhydrous ethanol with a volume ratio of 1:1 are weighed, the raw material powder is added to the anhydrous ethanol, and dispersed for 30 minutes using ultrasonic equipment to obtain a uniformly mixed slurry; the mixed slurry is poured into a ball mill, carbide balls are added, the ball milling speed and ball milling time are set, and the slurry is fully ground by alternating forward and reverse rotation; the ball milled slurry is transferred to a vacuum drying oven, and heated and dried for 7 hours under a vacuum pressure environment; the dried powder is taken out, and the powder is coarsely screened with an 80-mesh screen, and then finely screened with a 300-mesh screen to obtain a thermal spraying powder with impurities removed.

[0070] In this optional embodiment, the mass fraction of the tungsten carbide powder in the raw material powder is 10%, and the nickel alloy powder is Ni60 powder.

[0071] In this optional embodiment, the ball milling speed is 80 rpm, the ball milling time is 6 hours, the forward rotation time is 1 hour, and the reverse rotation time is 0.5 hours.

[0072] In this optional embodiment, the vacuum pressure of the vacuum drying oven is less than 0.1 MPa, and the drying temperature is 70°C.

[0073] In this optional embodiment, the sandblasting pressure of the sandblasting treatment is 0.4-0.6Mpa, and the roughness of the surface of the connecting hardware after the sandblasting treatment is 10-15μm.

[0074] In this optional embodiment, when the thermal spray powder is fed into the powder spray gun and the flame spray process is used to uniformly coat the connection of the connecting hardware substrate to form a thermal spray coating, the connecting hardware substrate can be preheated to 300°C; the jet flow rate of the oxygen-acetylene mixed gas is controlled, the thermal spray powder is fed into the powder spray gun, and is sprayed at high speed to the connection of the connecting hardware substrate by compressed air until the entire coating area is uniformly coated; after waiting for the connecting hardware substrate to cool naturally after the thermal spraying is completed, the coating area is remelted to densify the coating expressed by the connecting hardware, and after the remelting is completed, the thermal stress is released by natural cooling to form a thermal spray coating at the connection of the connecting hardware substrate.

[0075] In this optional embodiment, the oxygen flow rate in the oxygen-acetylene mixed gas is 20 L / min, and the acetylene flow rate is 10 L / min.

[0076] In this optional embodiment, the distance between the powder spray gun and the surface of the connection hardware base is 100 mm, the spray angle is 70°, and the moving speed of the powder spray gun is 10-20 mm per second.

[0077] In this optional embodiment, the anti-corrosion coating includes a primer and a topcoat, and the primer is a water-based zinc-rich epoxy anti-corrosion coating, and the topcoat is a water-based polyurethane coating.

[0078] Figure 2 An embodiment of an overhead power transmission line connection fitting of the present invention is shown.

[0079] In this optional embodiment, the overhead transmission line connecting fittings include a connecting fitting base, the connecting parts of the connecting fitting base are coated with a thermal spray coating, and the surface of the connecting fitting base is sprayed with an anti-corrosion coating.

[0080] In this optional embodiment, the material of the connecting hardware substrate is 35CrMo, the thermal spray coating is made by flame spraying process, the raw material of the thermal spray coating is thermal spray powder composed of tungsten carbide powder and nickel alloy powder, and the mass fraction of tungsten carbide powder in the thermal spray powder is 10%, and the nickel alloy powder is Ni60 powder.

[0081] In this optional embodiment, the anti-corrosion coating includes a primer and a topcoat, the primer is a water-based zinc-rich epoxy anti-corrosion coating, and the topcoat is a water-based polyurethane coating.

[0082] In this optional embodiment, the water-based zinc-rich epoxy anti-corrosion coating includes component A and component B in a mass ratio of 5:4; the component A includes the following raw materials in mass parts: 15-20 parts of water-based epoxy curing agent, 75-100 parts of spherical zinc powder, 1-2 parts of defoaming agent and 0.5-2 parts of surface wetting agent; the component B includes the following raw materials in mass parts: 20-25 parts of water-based epoxy resin, 3-5 parts of polyaniline-modified halloysite nanotubes, 1-2 parts of thickener, 10-15 parts of deionized water, 1-2 parts of defoaming agent, and 0.5-1 part of anti-flash rust agent.

[0083] In this optional embodiment, the water-based zinc-rich epoxy anti-corrosion coating includes component A and component B in a mass ratio of 5:4; the component A includes the following raw materials in mass: 15g of water-based epoxy curing agent, 75g of spherical zinc powder, 1g of defoaming agent and 0.5g of surface wetting agent; the component B includes the following raw materials in mass: 20g of water-based epoxy resin, 3g of polyaniline-modified halloysite nanotubes, 1g of thickener, 10g of deionized water, 1g of defoaming agent and 0.5g of anti-flash rust agent.

[0084] In this optional embodiment, the water-based zinc-rich epoxy anti-corrosion coating includes component A and component B in a mass ratio of 5:4; the component A includes the following raw materials in mass parts: 17g of water-based epoxy curing agent, 85g of spherical zinc powder, 1.5g of defoaming agent and 1g of surface wetting agent; the component B includes the following raw materials in mass parts: 22.5g of water-based epoxy resin, 4g of polyaniline-modified halloysite nanotubes, 1.5g of thickener, 12.5g of deionized water, 1.5g of defoaming agent and 0.75g of anti-flash rust agent.

[0085] In this optional embodiment, the water-based zinc-rich epoxy anti-corrosion coating includes component A and component B in a mass ratio of 5:4; the component A includes the following raw materials in mass: 20g of water-based epoxy curing agent, 100g of spherical zinc powder, 2g of defoaming agent and 2g of surface wetting agent; the component B includes the following raw materials in mass: 25g of water-based epoxy resin, 5g of polyaniline-modified halloysite nanotubes, 2g of thickener, 15g of deionized water, 2g of defoaming agent and 1g of anti-flash rust agent.

[0086] In this optional embodiment, the water-based polyurethane coating includes a C component and a D component in a mass ratio of 5:2; the C component includes the following raw materials in parts by weight: 20-25 parts of aqueous hydroxypropyl emulsion, 5-10 parts of aluminum powder, 1-2 parts of titanium dioxide, 3-5 parts of boron nitride nanosheets, 15-20 parts of deionized water, 1-2 parts of wetting dispersant, and 0.3-0.5 parts of defoaming agent; the D component includes the following raw materials in parts by mass: 5-8 parts of isocyanate curing agent and 6-10 parts of propylene glycol methyl ether acetate.

[0087] In this optional embodiment, the water-based polyurethane coating includes component C and component D in a mass ratio of 5:2; the component C includes the following raw materials in parts by weight: 20g of water-based hydroxypropyl emulsion, 5g of aluminum powder, 1g of titanium dioxide, 3g of boron nitride nanosheets, 15g of deionized water, 1g of wetting dispersant, and 0.3g of defoaming agent; the component D includes the following raw materials in parts by mass: 5g of isocyanate curing agent and 6g of propylene glycol methyl ether acetate.

[0088] In this optional embodiment, the water-based polyurethane coating includes component C and component D in a mass ratio of 5:2; the component C includes the following raw materials in parts by weight: 22.5g of water-based hydroxypropyl emulsion, 7.5g of aluminum powder, 1.5g of titanium dioxide, 4g of boron nitride nanosheets, 17.5g of deionized water, 1.5g of wetting dispersant, and 0.4g of defoaming agent; the component D includes the following raw materials in parts by mass: 7g of isocyanate curing agent and 8g of propylene glycol methyl ether acetate.

[0089] In this optional embodiment, the water-based polyurethane coating includes component C and component D in a mass ratio of 5:2; the component C includes the following raw materials in parts by weight: 25g of water-based hydroxypropyl emulsion, 10g of aluminum powder, 1-2g of titanium dioxide, 5g of boron nitride nanosheets, 20g of deionized water, 2g of wetting dispersant, and 0.5g of defoaming agent; the component D includes the following raw materials in parts by mass: 8g of isocyanate curing agent and 10g of propylene glycol methyl ether acetate.

[0090] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0091] The connection fittings of the present invention are realized by the following technical solutions:

[0092] 1. Selection of base material for connection hardware: The base material is 35CrMo, which is treated with quenching and tempering to improve its strength and toughness, ensuring its long-term stability in harsh environments. The quenching and tempering parameters are: quenching after heating at 875℃, and tempering temperature after quenching at 550℃ for 2 hours.

[0093] 2. Preparation of thermal spray powder materials:

[0094] The first step is to prepare raw material powders, select WC powder with an average particle size of 30 μm and Ni60 powder with a particle size of 40-60 μm, and the mass fraction of WC powder is 10%.

[0095] The second step is to prepare the slurry. Add the raw material powder into anhydrous ethanol at a volume ratio of 1:1. Use ultrasonic equipment for dispersion, and the ultrasonic dispersion time is 30 minutes to ensure that the powder raw material is fully dispersed in anhydrous ethanol.

[0096] The third step is ball milling. Pour the mixed slurry into a ball mill, add YG8 carbide balls with a diameter of 8 mm, the mass ratio of ball milling medium to slurry is 3:1, the ball milling speed is set to 80 rpm, the ball milling time is 6 hours, 1 hour forward and 0.5 hour reverse, alternating.

[0097] Step 4: Drying: The slurry obtained after ball milling was transferred to a vacuum drying oven, and the drying temperature was set to 70°C and the drying time was set to 10 hours under a vacuum pressure of <0.1 MPa.

[0098] Step 5: Screening: The dried powder is first screened with an 80-mesh sieve to remove larger particles and impurities; then screened with a 300-mesh sieve to remove fine impurities to ensure the purity of the powder.

[0099] 3. Sandblasting of the hardware surface before thermal spraying: The sandblasting pressure is controlled at 0.4-0.6MPa to coarsen the surface of the workpiece and the roughness Ra reaches 10-15μm.

[0100] 4. Flame spraying process:

[0101] 1. The preheating temperature of the workpiece is controlled at around 300°C.

[0102] 2. Oxygen-acetylene mixed gas control, oxygen flow rate is 20min (optional range is 20-25L / min), acetylene flow rate is 10L / min (optional range is 20-25L / min).

[0103] 3. Ni60 powder is fed into the powder spray gun and sprayed at high speed to the connection of the fittings by compressed air (see figure). The distance between the spray gun and the workpiece surface is controlled at about 100mm, the spray angle is 75°, and the movement speed of the spray gun is controlled at about 20mm per second (the optional range is 10-20mm).

[0104] 4. After the alloy powder is evenly coated on the surface by thermal spraying, the coated area is remelted after the workpiece cools naturally to densify the coating on the surface of the hardware and create a stronger metallurgical bond with the substrate. After remelting, natural cooling is used to gradually release thermal stress.

[0105] 5. Preparation of anti-corrosion coating for hardware

[0106] The hardware primer uses water-based zinc-rich epoxy anti-corrosion paint, and the topcoat uses water-based polyurethane paint.

[0107] The water-based zinc-rich epoxy anti-corrosion coating is composed of component A and component B, and the mass ratio of component A to component B is 5:4, wherein component A includes the following raw materials in parts by weight: 15-20 parts of water-based epoxy curing agent, 75-100 parts of spherical zinc powder, 1-2 parts of defoaming agent and 0.5-2 parts of surface wetting agent; component B includes the following raw materials in parts by weight: 20-25 parts of water-based epoxy resin, 3-5 parts of polyaniline-modified halloysite nanotubes, 1-2 parts of thickener, 10-15 parts of deionized water, 1-2 parts of defoaming agent and 0.5-1 part of anti-flash rust agent.

[0108] Specifically, the waterborne epoxy curing agent is Epikure 8538-Y-68, and the active hydrogen equivalent is 300 g / eq; the defoaming agent is BYK022; the surface wetting agent is BYK349; the waterborne epoxy resin is Epikote 6520-WH-50, and the epoxy equivalent is 500-600 g / eq; the thickener is PUR-64 or hydroxyethyl cellulose; and the flash rust inhibitor is a 5% sodium nitrite aqueous solution.

[0109] The preparation method of polyaniline-modified halloysite nanotubes is as follows: 5 g of halloysite nanotubes are dispersed in 1 L of hydrochloric acid aqueous solution, followed by adding 5 g of aniline, and after sufficient mixing, the suspension is placed in an ice-water bath and stirred for 1 hour. 23 g of ammonium persulfate is added dropwise to the suspension for 0.5 hours. After the reaction solution is reacted at low temperature for 1 hour, the ice-water bath is removed and reacted at room temperature for 12 hours. After the reaction is completed, the suspension is centrifuged and washed with water 3 times to obtain polyaniline-modified halloysite nanotubes.

[0110] The waterborne polyurethane coating is composed of a component C and a component D, wherein the mass ratio of the component C to the component D is 5:2, wherein the component C comprises the following raw materials in parts by weight: 20-25 parts of waterborne hydroxypropyl emulsion, 5-10 parts of aluminum powder, 1-2 parts of titanium dioxide, 3-5 parts of boron nitride nanosheets, 15-20 parts of deionized water, 1-2 parts of a wetting dispersant, and 0.3-0.5 parts of a defoaming agent; and the component D comprises the following raw materials in parts by weight: 5-8 parts of an isocyanate curing agent and 6-10 parts of propylene glycol methyl ether acetate.

[0111] Specifically, the water-based hydroxypropyl emulsion is A145, and the hydroxyl content is 3.5%; the isocyanate curing agent is 2655, and the isocyanate content is 21%.

[0112] The preparation method of boron nitride nanosheets is as follows: boron nitride powder is added to an aqueous solution containing a copolymer of perfluoro-3,6-diepoxy-4-methyl-7-decene-sulfuric acid, and ultrasonicated for 12 hours. After completion, the suspension is centrifuged, washed with water three times, and dried after centrifugation to obtain boron nitride nanosheets.

[0113] Example 1

[0114] 1. Selection of base material. The base material of the U-shaped hanging ring U-10 is 35CrMo steel, which is tempered to improve strength and toughness. The tempering treatment parameters are heating at 875℃ and oil quenching, followed by tempering at 550℃ for 2 hours.

[0115] 2. Thermal spraying powder material selection: Ni60 coated tungsten carbide powder is used, the mass fraction of tungsten carbide is 10%, and the particle size is controlled at 70±15 microns.

[0116] 3. Surface treatment before thermal spraying: The surface of the hardware is sandblasted to a surface roughness Ra of 12μm.

[0117] 4. Flame spraying process: The workpiece is preheated to 300°C and the oxygen-acetylene flame spraying process is adopted. The oxygen flow rate is 22L / min and the acetylene flow rate is 10L / min. The Ni60 coating powder is sprayed to the workpiece surface at high speed by compressed air. The distance between the spray gun and the workpiece surface is kept at 100mm, the spray angle is 75°, and the spray gun moves at a speed of 20mm per second. After the coating is completed, a remelting treatment is carried out to ensure the metallurgical bonding of the coating and the substrate, and finally natural cooling is adopted to release thermal stress. And the coating area is as follows Figure 3 shown.

[0118] Example 2

[0119] 1. Selection of base material. The base material of the U-shaped hanging ring U-10 is 35CrMo steel, which is tempered to improve strength and toughness. The tempering treatment parameters are heating at 875℃ and oil quenching, followed by tempering at 550℃ for 2 hours.

[0120] 2. Thermal spraying powder material selection: Ni60 coated tungsten carbide powder is used, the mass fraction of tungsten carbide is 20%, and the particle size is controlled at 70±15 microns.

[0121] 3. Surface treatment before thermal spraying: The surface of the hardware is sandblasted to a surface roughness Ra of 12μm.

[0122] 4. Flame spraying process: The workpiece is preheated to 300°C and the oxygen-acetylene flame spraying process is adopted, with an oxygen flow rate of 22L / min and an acetylene flow rate of 10L / min. The Ni60 coated powder is sprayed onto the workpiece surface at high speed by compressed air, the distance between the spray gun and the workpiece surface is maintained at 100mm, the spray angle is 75°, and the spray gun moves at a speed of 20mm per second. After the coating is completed, a remelting treatment is carried out to ensure the metallurgical bonding of the coating and the substrate, and finally natural cooling is adopted to release thermal stress.

[0123] Comparative Example 1

[0124] 1. Selection of base material. The base material of the U-shaped hanging ring U-10 is 35CrMo steel, which is tempered to improve strength and toughness. The tempering treatment parameters are heating at 875℃ and oil quenching, followed by tempering at 550℃ for 2 hours.

[0125] 2. Thermal spraying powder material selection: Ni60 coated tungsten carbide powder is used, the mass fraction of tungsten carbide is 30%, and the particle size is controlled at 70±15 microns.

[0126] 3. Surface treatment before thermal spraying: The surface of the hardware is sandblasted to a surface roughness Ra of 12μm.

[0127] 4. Flame spraying process: The workpiece is preheated to 300°C and the oxygen-acetylene flame spraying process is adopted, with an oxygen flow rate of 22L / min and an acetylene flow rate of 10L / min. The Ni60 coated powder is sprayed onto the workpiece surface at high speed by compressed air, the distance between the spray gun and the workpiece surface is maintained at 100mm, the spray angle is 75°, and the spray gun moves at a speed of 20mm per second. After the coating is completed, a remelting treatment is carried out to ensure the metallurgical bonding of the coating and the substrate, and finally natural cooling is adopted to release thermal stress.

[0128] Comparative Example 2

[0129] 1. Selection of base material. The base material of the U-shaped hanging ring U-10 is 35CrMo steel, which is tempered to improve strength and toughness. The tempering treatment parameters are heating at 875℃ and oil quenching, followed by tempering at 550℃ for 2 hours.

[0130] 2. Thermal spraying powder material selection: Ni60 powder, particle size controlled at 70±15 microns, does not contain tungsten carbide.

[0131] 3. Surface treatment before thermal spraying: The surface of the hardware is sandblasted to a surface roughness Ra of 12μm.

[0132] 4. Flame spraying process: The workpiece is preheated to 300°C and the oxygen-acetylene flame spraying process is adopted, with an oxygen flow rate of 22L / min and an acetylene flow rate of 10L / min. The Ni60 coated powder is sprayed onto the workpiece surface at high speed by compressed air, the distance between the spray gun and the workpiece surface is maintained at 100mm, the spray angle is 75°, and the spray gun moves at a speed of 20mm per second. After the coating is completed, a remelting treatment is carried out to ensure the metallurgical bonding of the coating and the substrate, and finally natural cooling is adopted to release thermal stress.

[0133] Comparative Example 3

[0134] The U-shaped hanging ring U-10 made of tempered 35CrMo steel was selected without thermal spraying treatment.

[0135] Comparative Example 4

[0136] The U-shaped hanging ring U-7 made of tempered Q345 steel was selected without thermal spraying treatment.

[0137] The finished products prepared by Examples 1-2 and Comparative Examples 1-4 were obtained, and the characteristics and performance of each finished product were demonstrated by means of experiments and data recording, such as Figure 2 , Figure 4-Figure 7 As shown, the details are as follows.

[0138] Figure 2The morphology and particle size distribution characteristics of nickel-based tungsten carbide powder synthesized by ball milling are given. The alloy particles with 10% WC added are slightly irregular in morphology, and some particles have a slight roughness on the surface. This is because the addition of WC affects the spheroidization process of the powder, resulting in some particles unable to form a perfect sphere during the cooling process. However, the overall morphology is still mainly spherical, which shows that the addition of 10% WC does not significantly damage the formability of the powder. The surface morphology of the alloy powder with 20% WC added becomes more complex, with more irregular particles and a rougher surface. This is because the increase in WC content causes the alloy powder to undergo a large deformation during the solidification process, and some WC particles are exposed on the powder surface, resulting in an increase in surface roughness. With the further increase in WC content, the morphology of the 30% WC powder particles becomes more irregular, and some particles even show the characteristics of incomplete melting. This shows that the high content of WC leads to poor spheroidization of the powder during the spraying process, thereby affecting the overall morphology of the powder. The particle size distribution of 30% WC alloy powder is further expanded, and the particle size range is mainly between 40-120 μm. Such distribution characteristics mean that the powder will produce large splashes during the spraying process, which will affect the coating quality.

[0139] Figure 4 The microhardness distribution results from the outermost surface of the coating to the substrate layer of Example 1, Example 2, Comparative Example 1, and Comparative Example 2 are given. Among them, the surface hardness of Comparative Example 2 with a WC addition of 0% is 800-900HV, showing a good hardness, while the surface hardness of the sample of Example 1 with a WC addition of 10% is the highest, close to 960HV. The appropriate amount of WC significantly improves the hardness of the coating. The surface hardness of Example 2 with a WC addition of 20% and Comparative Example 1 with a WC addition of 30% is about 900HV. Although the WC content is further increased, the hardness does not increase significantly, but decreases slightly. This is due to the internal unevenness or increased porosity of the coating caused by excessive WC particles. The hardness of Comparative Example 2 with a WC addition of 0% begins to slowly decrease at a depth of 0.3mm, and drops to the substrate hardness level at 0.7mm, indicating that there is a certain transition zone between the coating and the substrate. The hardness of Example 1 with 10% WC addition also starts to decrease at 0.3mm, but the decrease is more rapid than that of Ni-WC0, and reaches the matrix hardness at 0.5mm. The hardness of Example 2 with 20% WC addition and Comparative Example 1 with 30% WC addition starts to decrease at 0.1mm, and decreases rapidly, and approaches the matrix hardness at 0.3mm, and the hardened layer is thin.

[0140] Figure 5The open circuit potential and polarization curves of four samples, Example 1, Example 2, Comparative Example 1, and Comparative Example 2, in 3.5wt.% NaCl solution are given. The open circuit potential reflects the stability and thermodynamic information of the coating in a corrosive environment. It can be seen that as the corrosion progresses, the open circuit potential of Comparative Example 2 with a WC addition of 0% remains almost unchanged, indicating that the coating has good stability and good corrosion resistance. The open circuit potential of Example 1 with a WC addition of 10% and Example 2 with a WC addition of 20% gradually decreases over time, but the amplitude is small, indicating that after the addition of WC, although the coating shows some slight electrochemical instability, it still has good thermodynamic stability as a whole. The open circuit potential curve of Comparative Example 1 with a WC addition of 30% fluctuates greatly, showing obvious electrochemical instability. This shows that under the condition of high WC content (30%), the uniformity of the coating is significantly reduced, and the increase in pores and cracks makes the coating susceptible to corrosion by corrosive media. From the perspective of polarization curves, the corrosion current density of Comparative Example 2 with a WC addition of 0% is the lowest and the corrosion potential is the highest, indicating that the Ni-based alloy has good corrosion resistance. This is attributed to the fact that the Ni-based alloy can form a stable passivation film in a saline solution, thereby preventing further corrosion. In comparison, the corrosion current density of Example 1 with a WC addition of 10% and Example 2 with a WC addition of 20% increased, and the corrosion potential decreased slightly. This is because the presence of WC particles introduces local electrochemical inhomogeneity, leading to an increase in corrosion rate. With the increase of WC content, the corrosion current density of Comparative Example 1 with a WC addition of 30% further increased, and the corrosion potential decreased, showing a higher corrosion tendency. The aggregation of WC particles and the increase in pores at the interface make it easier for the corrosive medium to enter and accelerate the corrosion process.

[0141] Figure 6The change of friction coefficient over time in friction and wear experiments of four samples is given. Compared with Comparative Example 2 without adding WC, Example 1, Example 2 and Comparative Example 1 samples show a lower friction coefficient. Although the Ni-WCO coating already has a high hardness (about 900HV) and contains hard phases such as Cr-C and Cr-B, however, after adding WC, the friction coefficient is significantly reduced. This can be attributed to the unique characteristics of WC and its role in the coating. First, WC particles have an extremely high hardness (usually up to 2000-3000HV), which enables them to form a hard protective layer during the friction process and reduce wear. At the same time, WC particles also have a certain lubricating effect, which can effectively reduce friction and reduce the sliding friction of the coating surface. Even if other hard phases already exist in the coating, the addition of WC can still significantly improve the friction performance. In addition, the high hardness and wear resistance of WC make it difficult to be worn or cut off during the friction process, thereby reducing the surface roughness and reducing microscopic irregularities. This smooth surface further reduces the friction coefficient. The uniform distribution of WC particles changes the wear mode, making the wear mainly manifest as slight abrasive wear or oxidative wear, which are usually accompanied by a lower friction coefficient. On the other hand, the presence of WC particles can effectively disperse the stress of the friction contact surface, avoid material yield and wear caused by stress concentration, and thus maintain a low friction coefficient.

[0142] Figure 7 (a) shows the wear scar morphology and two-dimensional wear scar profile of Example 1 after the friction and wear test. The wear scar surface of the sample is relatively flat, but one-dimensional wear marks can still be observed along the wear scar direction, indicating that there is a certain degree of abrasive wear during the wear process of the sample. In addition, the wear scar area is narrow, and the maximum depth of the wear scar is about 10μm. The addition of WC significantly improves the wear resistance of the coating, making the material show stronger wear resistance under the same wear conditions.

[0143] Figure 7(b) shows the wear scar morphology and two-dimensional wear scar contour of Example 2 after the friction and wear test. Compared with Example 1, the wear scar area of ​​Example 2 is slightly rough, and there are a large number of one-dimensional wear marks along the wear scar direction on the wear scar surface. This shows that the increase in WC content leads to a greater degree of abrasive wear of the material during the friction process. In addition, the wear scar area of ​​Example 2 is also slightly wider than that of Example 1, and some pits can still be observed in the wear scar, which shows that the increase in WC content cannot completely eliminate the micro-flaking phenomenon in the wear scar. The maximum wear scar depth of Example 2 is about 15μm. Compared with Example 1, the wear scar depth of the coating of Example 2 increases slightly. This is because the excessive WC content increases the internal heterogeneity of the coating, thereby reducing the overall wear resistance of the coating. Although the addition of WC enhances the wear resistance of the coating, the excessively high WC content leads to more defects in the coating, such as pores or microcracks, which aggravates the wear during the friction process.

[0144] Figure 7 (c) shows the wear scar morphology and two-dimensional wear scar profile of Comparative Example 1 after the friction and wear test. Compared with Example 1 and Example 2, the wear scar area of ​​Comparative Example 1 appears to be rougher, and there are more obvious wear marks on the wear scar surface. The wear scar area is significantly widened, and more pits and uneven areas can be observed in the wear scar, which indicates that the high content of WC fails to significantly improve the micro-flaking phenomenon of the coating during the friction process, and even aggravates the formation of these defects. Compared with Example and Example 2, the wear scar depth of the coating of Comparative Example 1 is further increased, indicating that the excessively high WC content leads to an increase in the unevenness of the internal structure of the coating, thereby reducing the overall wear resistance of the coating. Although the addition of WC helps to enhance the hardness and wear resistance of the coating in the early stage, when the WC content is too high, more defects such as pores or microcracks will be formed in the coating. These defects are easy to become the starting point of wear extension during the friction process, and ultimately lead to a decrease in the wear resistance of the coating.

[0145] Figure 7 (d) shows the wear scar morphology and two-dimensional wear scar contour of Comparative Example 2 after the friction and wear test. The wear scar area clearly shows the material removal characteristics during the wear process. The wear scar surface is relatively flat, but one-dimensional wear marks can be observed along the wear scar direction, indicating that the material has undergone obvious material removal under the action of friction. In addition, there are some small pits in the area around the wear scar, which are caused by microscopic peeling of the material during the friction process. The maximum depth of the wear scar is close to 40μm. Compared with the wear depth of less than 15μm of the materials of Examples 1 and 2 under the same wear conditions, the coating of Comparative Example 2 exhibits lower wear resistance.

[0146] The present invention is not limited to the structures which have been described above and shown in the drawings, and various modifications and changes may be made without departing from the scope thereof. The scope of the present invention is limited only by the appended claims.

Claims

1. A method for preparing a connecting fitting for an overhead power transmission line, characterized in that: include: Selecting the base material of the connection fittings, and obtaining the connection fitting base through quenching and tempering treatment; Selecting tungsten carbide powder and nickel alloy powder to form raw material powder, and using ball milling and screening process to remove impurities from the raw material powder to obtain thermal spraying powder; Performing sandblasting on the surface of the connection hardware base to roughen the surface of the connection hardware base; The thermal spraying powder is fed into a powder spray gun, and the connection of the connection hardware substrate is evenly coated by a flame spraying process to form a thermal spray coating; An anti-corrosion coating is sprayed on the surface of the connecting hardware base to obtain a wear-resistant and corrosion-resistant connecting hardware.

2. The method for preparing the connecting fittings for overhead power transmission lines according to claim 1, characterized in that: The base material is 35CrMo, and the tempering treatment includes heating to 875°C and then quenching, the tempering temperature after quenching is 550°C, and the tempering time is 2h.

3. The method for preparing the connecting fittings for overhead power transmission lines according to claim 1, characterized in that: The raw material powder is composed of tungsten carbide powder and nickel alloy powder, and the raw material powder is subjected to impurity removal treatment by ball milling and screening process to obtain thermal spraying powder, which includes: Select tungsten carbide powder with an average particle size of 30 μm and nickel alloy powder with a particle size of 40-60 μm, mix them to form raw material powder; Weigh raw material powder and anhydrous ethanol in a volume ratio of 1:1, add the raw material powder into the anhydrous ethanol, and disperse it by ultrasonic equipment for 30 minutes to obtain a uniformly mixed slurry; Pour the mixed slurry into a ball mill, add carbide balls, set the ball mill speed and time, alternately rotate forward and reverse to fully grind the slurry; The ball-milled slurry was transferred to a vacuum drying oven and dried under vacuum pressure for 7 hours; The dried powder was taken out, and the powder was coarsely screened with an 80-mesh screen, and then finely screened with a 300-mesh screen to obtain a thermal spray powder with impurities removed.

4. The method for preparing the connecting fittings for overhead power transmission lines according to claim 3, characterized in that: The mass fraction of the tungsten carbide powder in the raw material powder is 10%, and the nickel alloy powder is Ni60 powder.

5. The method for preparing the connecting fittings for overhead power transmission lines according to claim 3, characterized in that: The ball milling speed is 80 rpm, the ball milling time is 6 h, the forward rotation time is 1 h, and the reverse rotation time is 0.5 h.

6. The method for preparing the connecting fittings for overhead power transmission lines according to claim 3, characterized in that: The vacuum pressure of the vacuum drying oven is less than 0.1 MPa, and the drying temperature is 70°C.

7. The method for preparing the connecting fittings for overhead power transmission lines according to claim 1, characterized in that: The blasting pressure of the sandblasting treatment is 0.4-0.6Mpa, and the roughness of the surface of the connecting hardware after the sandblasting treatment is 10-15μm.

8. The method for preparing the connecting fittings for overhead power transmission lines according to claim 1, characterized in that: The step of feeding the thermal spray powder into a powder spray gun and uniformly coating the connection of the connection hardware substrate using a flame spraying process to form a thermal spray coating comprises: Preheat the connection hardware base to 300°C; The jet flow rate of oxygen-acetylene mixed gas is controlled to feed the thermal spray powder into the powder spray gun, and the compressed air is sprayed at high speed to the connection of the connecting hardware substrate until the entire coating area is evenly coated; After waiting for the connection hardware substrate to cool naturally after thermal spraying, the coated area is remelted to densify the coating expressed by the connection hardware. After the remelting is completed, the thermal stress is released by natural cooling to form a thermal spray coating at the connection of the connection hardware substrate.

9. The method for preparing the connecting fittings for overhead power transmission lines according to claim 8, characterized in that: The oxygen flow rate in the oxygen-acetylene mixed gas is 20 L / min, and the acetylene flow rate is 10 L / min.

10. The method for preparing the connecting fittings for overhead power transmission lines according to claim 8, characterized in that: The distance between the powder spray gun and the surface of the connection hardware base is 100 mm, the spray angle is 70°, and the moving speed of the powder spray gun is 10-20 mm per second.

11. The method for preparing the connecting fittings for overhead power transmission lines according to claim 1, characterized in that: The anti-corrosion coating comprises a primer and a topcoat, wherein the primer is a water-based zinc-rich epoxy anti-corrosion coating, and the topcoat is a water-based polyurethane coating.

12. An overhead power transmission line connection fitting, characterized in that: It comprises a connecting hardware base, the connecting parts of which are coated with a thermal spray coating, and the surface of which is sprayed with an anti-corrosion coating.

13. The overhead power transmission line connection fitting according to claim 12, characterized in that: The material of the connection hardware substrate is 35CrMo, the thermal spray coating is made by flame spraying, the raw material of the thermal spray coating is thermal spray powder composed of tungsten carbide powder and nickel alloy powder, and the mass fraction of tungsten carbide powder in the thermal spray powder is 10%, and the nickel alloy powder is Ni60 powder.

14. The overhead power transmission line connection fitting according to claim 12, characterized in that: The anti-corrosion coating comprises a primer and a topcoat, wherein the primer is a water-based zinc-rich epoxy anti-corrosion coating, and the topcoat is a water-based polyurethane coating.

15. The overhead power transmission line connection fitting according to claim 14, characterized in that: The water-based zinc-rich epoxy anticorrosive coating comprises component A and component B in a mass ratio of 5:4; The component A comprises the following raw materials in parts by weight: 15-20 parts of waterborne epoxy curing agent, 75-100 parts of spherical zinc powder, 1-2 parts of defoaming agent and 0.5-2 parts of surface wetting agent; The B component includes the following raw materials in parts by weight: 20-25 parts of waterborne epoxy resin, 3-5 parts of polyaniline-modified halloysite nanotubes, 1-2 parts of thickener, 10-15 parts of deionized water, 1-2 parts of defoamer, and 0.5-1 part of anti-flash rust agent.

16. The overhead power transmission line connection fitting according to claim 14, characterized in that: The waterborne polyurethane coating comprises a C component and a D component in a mass ratio of 5:2; The C component includes the following raw materials in parts by weight: 20-25 parts of aqueous hydroxypropyl emulsion, 5-10 parts of aluminum powder, 1-2 parts of titanium dioxide, 3-5 parts of boron nitride nanosheets, 15-20 parts of deionized water, 1-2 parts of wetting and dispersing agent, and 0.3-0.5 parts of defoaming agent; The D component comprises the following raw materials in parts by weight: 5-8 parts of isocyanate curing agent and 6-10 parts of propylene glycol methyl ether acetate.

Citation Information

Patent Citations

  • Antiseptic super-hydrophobic paint for electric power system fittings and preparation method

    CN103642378A

  • Medium and low temperature curing organosilicone modified acrylic acid-polyurethane water-based coating and preparation method thereof

    CN109868047A

  • Preparation method of Ni60-WC remelting coating and Ni60-WC remelting coating

    CN115522158A

  • Preparation of functional microcapsule and application of functional microcapsule in anticorrosive paint

    CN118045538A

  • Corrosion-resistant sprayed coating, method for forming same and spraying device for forming same

    US20170015838A1